Response to “Familial Intracranial Aneurysm Requires Not Only Whole-Exome Sequencing, But Also Mitochondrial DNA Sequencing” - Suh, Dae Chul; Lee, Jong-Keuk; Seo, Eul-Ju (Korean journal of radiology, 2022)
KCI Citation Count: 0